Study of ChatGPT and Digital Literacy Influence on Learning Motivation Among College Student - Eunike, Prisca; Wardhani, Putri Ayu Puspieta; Wulansari, Oktufiani Dwi (JURNAL PENELITIAN PENDIDIKAN, PSIKOLOGI DAN KESEHATAN (J-P3K), 2024)
The increasing ease of learning for students in the era of technological advancement has led to a shift in students' learning motivation. Various platforms and applications can be utilized to support self-directed learning, one of which is through the existence of ChatGPT. However, the convenience offered by various technologies needs to be accompanied by good digital literacy skills. The aim of this study is to determine the impact of ChatGPT usage on student learning motivation. This research was conducted using a quantitative correlational design, by distributing an online form among students. The scale used was developed by the researchers based on indicators from existing theories and answered using a 5-point Likert scale rating. The analysis was performed using multiple regression methods. A total of 127 participants from various academic levels were obtained. The results of the study indicate that both ChatGPT usage and digital literacy together influence student learning motivation. Furthermore, ChatGPT alone does not have a significant impact, but it needs to be accompanied by digital literacy. These results emphasize the importance of understanding and mastering existing technologies before utilizing technological advancements to benefit student learning attitudes. Universities may consider providing training and guidance on the use of ChatGPT during the learning process to help enhance student motivation.